Effectiveness of Online Learning during The Covid-19 Pandemic in Deli Serdang District Junior High School - Ahmad Mukhlasin; Mansyur Hidayat Pasaribu (STAI Miftahul Ula Nganjuk, 2021)
The purpose of this study is to explain about the effectiveness of online learning during the covid-19 pandemic in junior high school in Deli Serdang Regency, North Sumatra, this research method is descriptive qualitative and conducted with online media, the result of this study is: The implementation of online learning in SMP Deli Serdang district contributes to habituation efforts in using online applications that are likely to grow in the future. Teachers' ability to choose learning methods and their skills in operationalizing online learning applications strongly supports the online learning process. All teachers of Deli Serdang District Junior High School are able to operate WhatsApp application even though it is not yet maximized. This online learning is considered ineffective in Deli Serdang Junior High School, because there are still obstacles such as: 1) quotas that must be purchased by students, 2) the assignments given always accumulate, 3) the conditions and circumstances of the student's home are different so that students must be divided into focus with other things, 4) understanding and explanation of the teacher has been delivered but less so directly understood by students so that they need help from others, 5) intrinsic motivation of students, lack of motivation to learn from parents. The success of the online learning system depends largely on some components of learning itself, whether from students, learning resource teachers, or information technology. .